Energy properties of rotational bands of 170-174Yb isotopes - Okhunov, Abdurahim; Anwer A.M, Al-Sammarrea; Tureva, Gulyuz (Institute of Physics Publishing, 2014)
Accounting for Coriolis mixing of experimentally known rotational bands non-adiabatic effects in energy of low-lying excited states are investigated, within phenomenological model. The Calculations for isotopes 170,172,174,176yb, are carried out.